Mechanisms of action and efficacy of statins against influenza - Mehrbod, Parvaneh; Omar, Abdul Rahman; Bejo, Mohd Hair; Haghani, Amin; Ideris, Aini (Hindawi Publishing Corporation, 2014)
The influenza virus (IV) is known to be a resistant virus with frequent mutations, causing severe respiratory diseases in the upper respiratory system. Public health concerns about clinical efficacy of all conventional drugs are ambiguous; therefore, finding additional therapeutic agents is critical to prevent and control influenza outbreaks. Influenza is associated with the induction of proinflammatory cytokines. Scientists have reported that anti-inflammatory drugs, with pleiotropic effects, reduce the burden of severe influenza diseases. Therefore, statins, which are cardioprotective drugs with anti-inflammatory and immunomodulatory effects, may help patients suffering from influenza virus (IV). This review delineates the potential use of statins as an alternative therapy in treating influenza related illness.